NECESIDAD DE IMPLEMENTAR MEDIDAS ALTERNATIVAS, RESPECTO A LA PRISIÓN DE LOS ALIMENTANTES DE BAJOS RECURSOS ECONÓMICOS QUE SE ENCUENTRAN IMPAGOS EN LAS PENSIONES ALIMENTICIAS, LAS CUALES GARANTICEN EL CUMPLIMIENTO DE SUS OBLIGACIONES - ESPINOSA HERRERA, WILMA DEL ROCIO (2016)
This paper whose topic called “NECESSITY OF ALTERNATIVE MEASURES IMPEMENTAR, REGARDING THE PRISON LOW INCOME OBLIGORS FOUND IN INMPAGOS ALIMONY, WHICH ENSURE COMPLIANCE WITH ITS OBLIGATIONS.” It aims to deepen a study of a social and legal, which is of great importance since those who are involved are minors who receive child support from a parent, who do not fulfill their obligation as parents, since they have no sufficient financial resources to do so, the lack of a permanent job would be one of the factors influencing the cancellation of maintenance, but if it is true that both the Constitution and the Code of Children and Adolescents, guaranteed rights of minors, even imposing coercive rules requiring comply with the provisions of the above statutes, but also should take into consideration the different cases of people of an economic disadvantage, that the prison will be unpaid, causing it harder to get the money to the respective cancellation, as they are limited, not only to comply with the relevant cancellation of pensions but also to have contact with their child or children, this implies consequent psychological damage that can result both the parent and the child, which is why the emphasis on this issue is raised for alternative measures of work by various social aid institutions, conducting a study of the respective socio-economic situation, that of one way or another contribute to parents who do not have to work in this way to ensure the payment of pensions, and not default on their responsibility in terms of maintenance